Faktor-faktor motivasi yang dipertimbangkan masyarakat dalam pemilihan sistem perbankan syariah (studi pada Bank BTN Syariah) - Seputra, R. Yudhistira Adi; Artha, Bhenu (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2021)
The purpose of this study was to determine the internal and external motivations considered by customers in saving funds at BTN Syariah Yogyakarta. This research was conducted on 110 respondents. The results showed that internal and external motivational factors were considered by customers in saving funds at BTN Syariah Yogyakarta. Further results show that there is no difference in the customer's internal and external motivations seen from the level of education and work.